Prevalence of Suicide Ideation and its Gender Distribution Among Undergraduate of University of Cape Coast, Cape Coast, Ghana - Adom-Mensah, Benedicta Ama; Bentil , Josephine Anterkyi; Lawer , Theresa Dede; Akoto , Justina Sarpong; Omotoshoe, Joshua A. (Journal of Advanced Psychology, 2022)
Purpose: The purpose of the study was to find out the prevalence of suicide ideation among undergraduate students of the University of Cape Coast and the gender distribution of suicide ideation among them. Methodology: This study was a quantitative one and it used the quasi-experimental research design, specifically, the pre-test, post-test and control group design. A total of 30 undergraduate students from four colleges of the University of Cape Coast in the Central Region of Ghana was non-randomly assigned to two treatment groups, Individual Psychology and Cognitive Behavioural Therapy (IP and CBT) and one control group. Beck Scale for Suicide Ideation was used for the collection of data for the study. Descriptive Statistics such as frequencies and percentages were used to analyse the data. Findings: Results showed that two out of every 15 UCC undergraduate students experience suicide ideation continuously and persistently. Again, the rate at which female students think suicidal, that is, have suicidal ideas, is higher than the male students. In other words, female undergraduate students of University of Cape Coast experience suicide ideation more than their male counterparts. It was concluded that suicide ideation is prevalent, 13.3%, among undergraduate students of UCC. Unique Contribution to Theory, Policy and Practice: Based on the findings, it was recommended that constant screening of suicide ideation be made part of the University's program and the Counselling Centre should be mandated to organise the screening exercise. This will help educate and create more awareness on suicide ideation and offer more people, per the screening, the opportunity to benefit from the therapies.